Improved Exciton Dissociation at Semiconducting Polymer:ZnO Donor:Acceptor Interfaces via Nitrogen Doping of ZnO. (7th March 2014) - Musselman, Kevin P.; Albert‐Seifried, Sebastian; Hoye, Robert L. Z.; Sadhanala, Aditya; Muñoz‐Rojas, David; MacManus‐Driscoll, Judith L.; Friend, Richard H.
<x xml:space="preserve">Abstract</x> Exciton dissociation at the zinc oxide/poly(3‐hexylthiophene) (ZnO/P3HT) interface as a function of nitrogen doping of the zinc oxide, which decreases the electron concentration from approximately 1019 cm−3 to 1017 cm−3, is reported. Exciton dissociation and device photocurrent are strongly improved with nitrogen doping. This improved dissociation of excitons in the conjugated polymer is found to result from enhanced light‐induced de‐trapping of electrons from the surface of the nitrogen‐doped ZnO. The ability to improve the surface properties of ZnO by introducing a simple nitrogen dopant has general applicability.